2013
DOI: 10.1111/trf.12078
|View full text |Cite
|
Sign up to set email alerts
|

Viability of umbilical cord blood mononuclear cell subsets until 96 hours after collection

Abstract: UCB manipulation did not influence cell viability. All cell subsets remained viable until 96 hours after collection. CD34+ cells and T lymphocytes increased, probably due to the loss of other subsets. CFU growth during the period analyzed and confirmed stem cell functionality, despite the decrease at 96 hours. Results demonstrated that UCB units could probably be processed up to 96 hours after collection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
3
9
0
Order By: Relevance
“…Venous human umbilical cord blood was taken from healthy term neonates into a blood bag system (Stemcare CB COLLECT™, Fresenius Kabi, Bad Homburg, Germany) and stored at room temperature until further processing within 24 hours [22]. The cells were separated using Biocoll separation solution (density 1.077 g/ml, isotone by Biochrom AG, Berlin, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Venous human umbilical cord blood was taken from healthy term neonates into a blood bag system (Stemcare CB COLLECT™, Fresenius Kabi, Bad Homburg, Germany) and stored at room temperature until further processing within 24 hours [22]. The cells were separated using Biocoll separation solution (density 1.077 g/ml, isotone by Biochrom AG, Berlin, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…According to these studies, the extending of the time from collection to processing determined a decrease in cell viability mainly for granulocyte, while the viability of CD34 + cells seems to not to be affected [7,21,22,28,34]. Thus, interested in knowing if a larger number of CD34 + cells ensure maintaining a higher cell viability, we noticed that there was a very reduced positive correlation (r = 0.0782; P < 0.0001) between these parameters.…”
Section: Tablementioning
confidence: 82%
“…Although previously it was demonstrated that there was no significant correlation between total cell viability (nucleated cell viability) and CD34 + cell viability, implying that the total cell viability might not be related to the functional state of progenitors cells [21,22], according to the US Food and Drug Administration recommendations, pre freezing nucleated cell viability is a quality control parameter and must be greater than 85% [23]. Our total cell viability assessment method by flow cytometry, using standardized protocol dedicated to clinical use, is the most effective method with high reproducibility between laboratories that follows ISHAGE (International Society of Hematotherapy and Graft Engineering) recommendations [24].…”
Section: Discussionmentioning
confidence: 96%
“…Whether these same effects are observed at 24 or 48 hours and whether further manipulation of the CBU (such as CD3+ cell depletion) affected the in vivo results were not tested. Further to this, a study by Pereira‐Cunha and colleagues suggests that, for donations stored at room temperature before cryopreservation for up to 96 hours, some cell subsets including mature and immature B lymphocytes and mesenchymal stem cells decrease during storage, whereas CD34+ cells remained constant. We have so far opted not to refrigerate donations before processing due to the difficulty of maintaining the low temperature at all stages of the production line.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have shown that the functionality of CD34+ cells can be reduced significantly after cryopreservation . In one of these studies, annexin V–negative CD34+ cells correlated with NOD/SCID mouse hematopoietic repopulating ability, indicating as would be expected that apoptotic CD34+ cells fail to engraft .…”
Section: Discussionmentioning
confidence: 98%